Prevalence of allergic conditions is higher in general paediatric inpatients than the general population – results of an inner-city general paediatric inpatient survey. (4th April 2011) - Loucaides, E M; Minshall, E; Gore, C
Abstract : Aims: Up to 30% of children of children in the UK suffer from allergic conditions. The prevalence of allergic co-morbidities among general paediatric inpatients is unclear. We surveyed the prevalence of allergic conditions among paediatric inpatients, how commonly these were recognised and listed on the discharge summary. Methods: Survey of 100 randomly selected patients admitted to a general paediatric ward in London. Survey period March to November 2010, one survey-day per week. Investigator administered questionnaire, to supplement medical admission history, exploring the spectrum of allergic diseases and frequency of symptoms. Survey of general paediatric discharge summaries relating to the inpatient episodes of patients who were interviewed to identify if any/all allergic conditions were communicated to general practitioner. Results: N=100 patients/parents were included, mean age 5.2 years, 62/100 (62%) male. 48/100 (48%) had at least one allergic condition, 6/100 (6%) had a probable allergic condition. 29/48 (60%) had one condition, 19/48 (40%) had ≥2 allergic conditions. Eczema was most frequent (30/100, 30%), followed by food allergy (19/100, 19%), asthma (16/100, 16%), allergic rhinitis (15/100, 15%), drug allergy (3/100, 3%). For 19/48 (40%) of children the allergic condition may have been relevant for the admission. Discharge summaries mentioned allergic conditions in 24/54 (44%) of children with definite/probable allergic diagnoses (20/24 in free text only); 13/54 (24%) expected allergy follow-up, 8/54(15%) were reviewed by an allergist, 4/54 (1%) had allergy tests carried out. Among definite cases (n=48) allergic rhinitis was never mentioned the discharge summary, eczema in 13/30 (43%), asthma in 9/16 (56%), food allergy in 13/19 (68%), drug allergy in 2/3 (67%). Relevant allergy related discharge medication was listed for: eczema 10/30 (33%), asthma 14/16 (88%), food allergy 2/19 (11%), allergic rhinitis 2/15 (13%). Conclusion: Allergic conditions were more prevalent in children admitted as inpatients than in the community (based on epidemiological studies). These allergic conditions were included in discharge summaries in less than half of the cases, relevant discharge medication was frequently omitted. Awareness of common allergic conditions, relevant history taking and communication with general practitioners need to be improved. Our results suggest a need for specific training as part of the undergraduate/postgraduate curriculum.